(ØªØÙ„ÙŠÙ„ ÙƒÙØ§Ø¡Ø© Ø§Ù„Ø·Ù„Ø§Ø¨ Ø¨Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ø¨Ø§Ù„Ù†Ø³Ø¨Ø© Ø¥Ù„Ù‰ Ù‚Ø¯Ø±ØªÙ‡Ù… ÙÙŠ Ø§Ù„Ù‚Ø±Ø§Ø¦Ø© ÙˆØ§Ù„ÙƒØªØ§Ø¨Ø© (Ø§Ù„Ø¥Ù…Ù„Ø§Ø¡ - Suparmanto Suparmanto (Lughatu Ad-Dhat, 2020)
ABSTRACT Based on the reality that occurred among students, especially in the eleventh semester of Nahdet Al-Watan Majidi High School, and on the research problems, which are how to analyze students ’proficiency in grammar in relation to their ability to read and write (dictation). In grammar and related to reading and writing especially with regard to spelling. As for the research method in which the researcher used, which is the qualitative research method and the data collection process in this research, namely: observation, interviews, documents, as well as the study of literature. The purpose of this study is to find out: Is there a significant relationship between students ’proficiency of grammar in relation to their ability to read and write (spelling)? Among the results and results is that the students ’efficiency and appropriation of the Arabic grammar, which is grammar and morphology at the Majidiyeh Institute, Nahdet al-Watan Majidi, was very good because it made the book reading program a preliminary program for this institute, but especially for the skill of writing (spelling), it needs the most attention and practice with the application always and without boredom So that students are skilled in writing sentences in Arabic. Keywords: grammar, reading, spelling.